CHANDA MISSION : A UNIQUE MISSION - Poovatholil, John (Asian Horizons, 2011)
Sambhaje Mahi Diyani, “Sharing everything dynamically divine,” in other words, consciously getting involved in the great process of redemption and development. With this Motto in their hearts and on their lips, the first six Missionaries from the Congregation of the Carmelites of Mary Immaculate (CMI), belonging to the Syro- Malabar Church of Oriental Rite, came to the newly erected Mission territory called Chanda, under the able guidance of his Excellency Bishop Januarius CMI, on 13 August 1962. In order to meet the new challenges and the great opportunities of evangelization and development of the Church in India the Holy See thought that the St Thomas Christians were vital. The history making event officially took place when Pope John XXlll by his apostolic decree “Ad Lucem Sancti Evangelii” established this new ecclesiastical Unit and entrusted it to the Congregation of the Carmelites of Mary Immaculate on 31 March 1962, for pioneer evangelization work. The formal handing over of the territory to Bp. Januarius by Msgr. Cassidy, the personal representative of the Apostolic Internuncio, took place on Wednesday, 15 August 1962, at a simple but impressive ceremony in the Chapel of the Archbishop’s house, Nagpur.